MorePork - RHoMIS midline survey of smallholder pig producers in Uganda - Ouma, Emily; Lukuyu, Ben A.; Lutakome, Pius; Hammond, James; Teufel, Nils (2023)
The dataset covers 688 pig farming households in Central Uganda. The RHoMIS midline survey was implemented in Nov-Dec 2021 and covers household farming practices, pig productivity and income indicators, as well as adoption of best practices and technologies for the pig enterprise.